Problems of Scientific Knowledge in the History of Philosophical Thought (In the Case of Central Asia) - Abdullayeva Khulkar Rakhmatullayevna (Central Asian Journal of Literature, Philosophy and Culture, 2022)
In the article, the views of Central Asian philosophers on knowledge, scientific knowledge, their contribution to epistemology are comprehensively disclosed. The directions of rationalism, sensualism, and empiricism have been studied. In the article, the development, progress, and specific directions of scientific knowledge in the researches of Farabi, Ibn Sina, and Beruni are analyzed in detail and in depth. He also touched on the issue of mutual influence of religion and scientific knowledge.